Towards Rational Design of a Toxoid Vaccine against the Heat-Stable Toxin of Escherichia coli - Taxt, Arne M. (Infect Immun, 2016)
Enterotoxigenic Escherichia coli (ETEC) is an important cause of diarrheal disease and death in children <5 years old. ETEC strains that express the heat-stable toxin (ST), with or without the heat-labile toxin, are among the four most important diarrhea-causing pathogens. This makes ST an attractive target for an ETEC vaccine. An ST vaccine should be nontoxic and elicit an immune response that neutralizes native ST without cross-reacting with the human endogenous guanylate cyclase C receptor ligands. To identify variants of ST with no or low toxicity, we screened a library of all 361 possible single-amino-acid mutant forms of ST by using the T84 cell assay. Moreover, we identified mutant variants with intact epitopes by screening for the ability to bind neutralizing anti-ST antibodies. ST mutant forms with no or low toxicity and intact epitopes are termed toxoid candidates, and the top 30 candidates all had mutations of residues A14, N12, and L9. The identification of nontoxic variants of L9 strongly suggests that it is a novel receptor-interacting residue, in addition to the previously identified N12, P13, and A14 residues. The screens also allowed us to map the epitopes of three neutralizing monoclonal antibodies, one of which cross-reacts with the human ligand uroguanylin. The common dominant epitope residue for all non-cross-reacting antibodies was Y19. Our results suggest that it should be possible to rationally design ST toxoids that elicit neutralizing immune responses against ST with minimal risk of immunological cross-reactivity.